Influence of the “five‑in‑one” mode on complications and compliance behaviors of patients with ureteral calculi after minimally invasive surgery - Xixian Ou; Xuejing Wang (Videosurgery and Other Miniinvasive Techniques)
Introduction: As a clinically common urinary system disease, ureteral calculus mainly manifests as hematuria and colicky pain.